Promoting universal financial protection: contracting faith-based health facilities to expand access - lessons learned from Malawi. - THOMAS, STEPHEN (My University, 2013)
Background Public-private collaborations are increasingly being utilized to universalize health care. In Malawi, the Ministry of Health contracts selected health facilities owned by the main faith-based provider, the Christian Health Association of Malawi (CHAM), to deliver care at no fee to the most vulnerable and underserved populations in the country through Service Level Agreements (SLAs). This study examined the features of SLAs and their effectiveness in expanding universal coverage. The study involved a policy analysis focusing on key stakeholders around SLAs as well as a case study approach to analyse how design and implementation of SLAs affect efficiency, equity and sustainability of services delivered by SLAs. Methods The study employed both qualitative and quantitative research methods to address the research questions and was conducted in five CHAM health facilities: Mulanje Mission, Holy Family, and Mtengowanthenga Hospitals, and Mabiri and Nkope Health Centres. National and district level decision makers were interviewed while providers and clients associated with the health facilities were surveyed on their experiences. A total of 155 clients from an expected 175 were recruited in the study. Results The study findings revealed key aspects of how SLAs were operating, the extent to which their objectives were being attained and why. In general, the findings demonstrated that SLAs had the potential to improve health and universal health care coverage, particularly for the vulnerable and underserved populations. However, the findings show that the performance of SLAs in Malawi were affected by various factors including lack of clear guidelines, non-revised prices, late payment of bills, lack of transparency, poor communication, inadequate human and material resources, and lack of systems to monitor performance of SLAs, amongst others. Conclusions There was strong consensus and shared interest between the government and CHAM regarding SLAs. It was clear that free services provided by SLAs had a great impact on the impoverished locals that used the facilities. However, lack of supporting systems, inadequate infrastructure and shortage of health care providers affected SLA performance. The paper provides recommendations to policy makers for the replication and strengthening of SLA implementation in the roll-out of universalization policy.
PUBLISHED
Keywords: Universal coverage; Policy analysis; Financial risk protection; Health policy; International Development